GE_GERICHTE P/6200/2024 vom 28. März 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;APPAREIL DE PRISE DE VUE ET/OU D'ENREGISTREMENT SONORE;DIFFAMATION;CALOMNIE;INJURE;MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);CHANTAGE | CPP.310; CP.179ter; CP.173; CP.174; CP.177; CP.180; CP.181; CP.156